2016
DOI: 10.1097/md.0000000000005114
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pharmacoeconomic research in China

Abstract: Background:The number of pharmacoeconomic publications in the literature from China has risen rapidly, but the quality of pharmacoeconomic publications from China has not been analyzed.Objectives:This study aims to identify all recent pharmacoeconomic publications from China, to critically appraise the reporting quality, and to summarize the results.Methods:Four databases (PubMed, Web of Science, Medline, and EmBase) were searched for original articles published up to December 31, 2014. The Consolidated Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The present study found that the number of health economic evaluations in the field of cardiac surgery has increased over time, and that the reporting quality has also improved. These findings are similar to those described elsewhere (18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study found that the number of health economic evaluations in the field of cardiac surgery has increased over time, and that the reporting quality has also improved. These findings are similar to those described elsewhere (18).…”
Section: Discussionsupporting
confidence: 93%
“…The assessment criteria used in the present study (CHEERS) have been applied in several systematic reviews reporting the quality of health economic publications (1821). There were several items that are partially or not reported by a large number of articles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the number of studies identified in this review compares favourably with previously published systematic reviews of the Chinese CEA literature 11 12 21. The most recently published review by Ma et al , which focused on study quality, included 32 pharmacoeconomic studies published up to 2014 12. Their review covered additional regions (studies relating to Special Administrative Regions, such as Hong Kong, were included) and also covered measures of effectiveness aside from the QALY or DALY.…”
Section: Discussionmentioning
confidence: 75%
“…Another systematic review of pharmacoeconomic publications produced in China between 2006 and 2012 included 20 studies 11. While another systematic review of the quality of pharmacoeconomic publications from China through 2014 included 32 studies 12…”
Section: Introductionmentioning
confidence: 99%
“…The number of published studies in China has increased from 91 in 1998 to 421 in 2007 to more than 1000 in 2016. 41,42 Malaysia has also developed pharmacoeconomic guidelines and is now towards the phase of implementation. Similarly, Indonesia has also adopted pharmacoeconomic guidelines which are being used by the Ministry of Health for clinical decision making.…”
Section: Asian Development In the Pharmacoeconomicsmentioning
confidence: 99%